Scoping reviews: time for clarity in definition, methods, and reporting - Colquhoun, Heather L.; Levac, Danielle; O'Brien, Kelly K.; Straus, Sharon; Tricco, Andrea C.; Perrier, Laure; Kastner, Monika; Moher, David (Journal of clinical epidemiology, 2014)
The scoping review has become increasingly popular as a form of knowledge synthesis. However, a lack of consensus on scoping review terminology, definition, methodology, and reporting limits the potential of this form of synthesis. In this article, we propose recommendations to further advance the field of scoping review methodology. We summarize current understanding of scoping review publication rates, terms, definitions, and methods. We propose three recommendations for clarity in term, definition and methodology. We recommend adopting the terms “scoping review” or “scoping study” and the use of a proposed definition. Until such time as further guidance is developed, we recommend the use of the methodological steps outlined in the Arksey and O'Malley framework and further enhanced by Levac et al. The development of reporting guidance for the conduct and reporting of scoping reviews is underway. Consistency in the proposed domains and methodologies of scoping reviews, along with the development of reporting guidance, will facilitate methodological advancement, reduce confusion, facilitate collaboration and improve knowledge translation of scoping review findings.